Distance higher education in Portugal: a disruptive strategy - Bento, P.; Sousa, H. (Economia Global e Gestão, 2012)
This paper looks into distance higher education (DHE) in Portugal and aims to devise an alternative strategy for its development. The proposed strategy results from a thorough analysis of DHE, preceded by a general appraisal of higher education (HE) and of the country itself, through which the following key conclusions were reached: as a consequence of timid or unsuccessful initiatives led by traditional universities, DHE in Portugal almost coincides with Universidade Aberta (UAb, the open university); amongst the challenges that HE faces, DHE represents a window of opportunities; by repeatedly putting off structural reformsa, the country is currently experiencing one of the most dramatic moments in its history. As an alternative to continuity, namely HE institutions following independent paths, coopetition stands out as a more beneficial route as it would be able to bring alignment and to generate synergies. A disruptive strategy in which UAb plays a central role is thus proposed.